Evangelical ecclesiology reality or illusion - Stackhouse, John Gordon, Jr, 1960-; Regent College, Vancouver, Canada, Theology Conference, 2002 (Grand Rapids, MI Baker Academic, 2003)
Includes bibliograhical references and indexes.
Papers from the Regent College Theology Conference (2002).
Keywords: Evangelicalism -- congresses